Museum spaces as psychological affordances: representations of immigration history and national identity - Mukherjee, Sahana; Salter, Phia S.; Molina, Ludwin E. (Frontiers in Psychology, 2015)
The present research draws upon a cultural psychological perspective to consider how psychological phenomena are grounded in socio-cultural contexts. Specifically, we examine the association between representations of history at Ellis Island Immigration Museum and identity-relevant concerns. Pilot study participants (N = 13) took a total of 114 photographs of exhibits that they considered as most important in the museum. Results indicate that a majority of the photographs reflected neutral themes (n = 81), followed by nation-glorifying images (n= 24), and then critical themes that highlight injustices and barriers faced by immigrants (n= 9). Study 1 examines whether there is a preference for glorifying images, and if that preference is related to cultural-assimilationist conceptions of national identity (i.e., defining American identity in dominant group standards). We exposed a new sample of participants (N = 119) to photographs reflecting all three themes. Results indicate that participants expressed greater liking for glorifying images, followed by neutral images, and critical images. National identity moderated within-subject variation in liking scores. Study 2 included 35 visitors who completed a survey before engaging with the museum or after their visit. Results indicate that participants who had completed their visit, compared to participants who had not entered the museum, reported (i) higher endorsement of cultural-assimilationist identity, and (ii) increased support for exclusive immigration policies. Study 3 exposed participants (N = 257) to glorifying, critical, or neutral images. Results indicate that participants who were exposed to glorifying images, especially those endorsing cultural-assimilationist identity, demonstrate decreased perception of current-day racial injustice, and increased ethnocentric enforcement bias. We discuss how engagement with privileged narratives may serve dominant group ends and reproduce systems of privilege.